2019
DOI: 10.20896/saci.v7i3.508
|View full text |Cite
|
Sign up to set email alerts
|

International Legal Format for Trans Regionalisation of Trade and Economic Partnership within BRICS in Global Development

Abstract: An integral part of globalisation is the emergence of a multipolar world. Strategic partnership at the regional, interregional and trans-regional levels is becoming a new institution and an instrument of modern international relations. The research discusses the international legal cooperation framework of BRICS (Brazil, Russia, India, China, South Africa) as a trans-regional association. The importance of rapprochement of the positions of the BRICS countries in the global political and economic system is emph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…One of the important indicators characterizing consumer spending as an important component of gross domestic product is the standard of living, i.e. the share of food expenditures in the general structure of household expenditures [32]. The population of Russia is still forced to spend a large part of its funds on the purchase of groceries, so by the end of 2018, the share of expenditures on the purchase of food products in the structure of household spending amounted to 33.5%.…”
Section: Resultsmentioning
confidence: 99%
“…One of the important indicators characterizing consumer spending as an important component of gross domestic product is the standard of living, i.e. the share of food expenditures in the general structure of household expenditures [32]. The population of Russia is still forced to spend a large part of its funds on the purchase of groceries, so by the end of 2018, the share of expenditures on the purchase of food products in the structure of household spending amounted to 33.5%.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, it should be concluded that the implementation of cluster policy is insufficient for the innovative transformation of the economy of Russian regions [11].…”
Section: Discussionmentioning
confidence: 99%
“…Features of the applied technology [2,3,5]: -high specific gravity of technically complex equipment;…”
Section: Methodsmentioning
confidence: 99%